Shelterin genes, germ line mutations and chronic lymphocytic leukemia - Slavutsky, Irma (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Telomeres are distinctive DNA-protein structures that cap the ends of linear chromosomes; they are essential to maintain chromosomal integrity and genome stability. Telomeres are composed by tandem repeats of the non-codificante DNA sequence TTAGGG bound by the shelterin complex. It contains six core proteins: telomeric repeat binding factor 1 (TERF1), TERF2, protection of telomeres 1 (POT1), adrenocortical dysplasia homolog (ACD), telomeric repeat-binding factor 2-interacting protein (TERF2IP) and TERF1 interacting nuclear factor 2 (TINF2), which play fundamental roles in telomere protection, chromosomal stability and regulation of telomere length (TL) (1). In addition, the shelterin complex modulates telomerase activity at chromosome ends, recognizes telomeric DNA and remodels it into a t-loop, which protects the 3’ overhang from being recognized as DNA damage. Alterations in the structure and function of any of these proteins may lead to undesirable DNA damage responses that could be associated to a role in tumorigenesis and cancer progression.